2014
DOI: 10.1007/s00268-014-2700-2
|View full text |Cite
|
Sign up to set email alerts
|

Parafibromin, Galectin‐3, PGP9.5, Ki67, and Cyclin D1: Using an Immunohistochemical Panel to Aid in the Diagnosis of Parathyroid Cancer

Abstract: A panel of immunohistochemistry (PGP9.5, galectin-3, parafibromin, and Ki67) is better than any single marker and can be used to supplement classical histopathology in diagnosing parathyroid cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 83 publications
1
50
2
1
Order By: Relevance
“…Recently, whole-genome sequencing uncovered additional mutations in parathyroid carcinomas, implicating PRUNE2 (∼18%), mTOR, MLL2, THRAP3 and PIK3CA genes 141 226 227. Overexpression of PGP9.5 (gene product of UCHL1 gene), galectin-3 and TERT (telomerase reverse transcriptase gene) were also described in some parathyroid carcinomas 160 223 230. Previous comparative genomic hybridisation and molecular allelotyping studies on parathyroid carcinomas also revealed losses on chromosomes 1p, 3, 13q and 14 and gains on chromosomes 1q and 16 42 141.…”
Section: Pathogenesis and Molecular Genetics Of Hptmentioning
confidence: 99%
“…Recently, whole-genome sequencing uncovered additional mutations in parathyroid carcinomas, implicating PRUNE2 (∼18%), mTOR, MLL2, THRAP3 and PIK3CA genes 141 226 227. Overexpression of PGP9.5 (gene product of UCHL1 gene), galectin-3 and TERT (telomerase reverse transcriptase gene) were also described in some parathyroid carcinomas 160 223 230. Previous comparative genomic hybridisation and molecular allelotyping studies on parathyroid carcinomas also revealed losses on chromosomes 1p, 3, 13q and 14 and gains on chromosomes 1q and 16 42 141.…”
Section: Pathogenesis and Molecular Genetics Of Hptmentioning
confidence: 99%
“…Even though the AUROC for parafibromin staining was 0.91 and the pooled specificity was 95 %, the pooled sensitivity was limited (68 %). Combined IHC analysis with other biomarkers such as galectin-3, Ki-67, p27, and protein gene product 9.5 (PGP95) was believed to be better than any single marker in diagnosing PTCA [27]. A significant heterogeneity was noted in sensitivity and specificity across included studies.…”
Section: Discussionmentioning
confidence: 97%
“…1. From 286 potentially relevant publications, a total of 10 studies were eligible for data extraction and analysis [15][16][17][23][24][25][26][27][28][29]. The characteristics of these included …”
Section: Eligible Articlesmentioning
confidence: 99%
“…Hence, it has been advocated that increased expression of PGP9.5 protein with loss of parafibromin nuclear staining should be used to screen for CDC73 mutation and PC [67,68]. Despite these restraints, the immunohistochemical panel that is usually used contains parafibromin, galactin-3, PGP9.5, and Ki-67 [70].…”
Section: Pathologic Diagnosismentioning
confidence: 99%